2003
DOI: 10.1074/jbc.m301597200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Induces the Expression of the SHARP-2/Stra13/DEC1 Gene via a Phosphoinositide 3-Kinase Pathway

Abstract: Transcription of the rat fatty acid synthase (FAS) gene in the rat liver can be regulated by feeding a high carbohydrate diet. A carbohydrate response element (ChoRE) located on the rat FAS gene promoter has been identified. Using multiple copies of the ChoRE as the bait in a yeast one-hybrid system, a rat liver cDNA library was screened, and the cDNA of ChoRE-binding proteins was cloned. A positive clone that encodes a basic helix-loop-helix protein, enhancer of split-and hairy-related protein-2 (SHARP-2), wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 44 publications
7
73
1
1
Order By: Relevance
“…Consistent with these data, insulin rapidly induces the expression of the Dec1 gene in primary hepatocytes (28). In the present study, we show that hepatic Dec1 expression levels are decreased in several NAFLD mouse models.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with these data, insulin rapidly induces the expression of the Dec1 gene in primary hepatocytes (28). In the present study, we show that hepatic Dec1 expression levels are decreased in several NAFLD mouse models.…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, Dec1 expression also can be induced by insulin and LXR␣ agonist (17,28). Of note, we also found that overexpression of Srebp-1c also decreased Dec1 expression in primary hepatocyte, although the exact molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 64%
“…As in our study, a recent report showed that BHLHB2 expression is induced by insulin in human muscle [2]. Although this remains to be demonstrated in muscle, this effect of insulin on BHLHB2 expression is likely to be mediated through the activation of the PI3-kinase pathway, as evidenced in rat liver [36]. Under such conditions, the impaired regulation of BHLHB2 expression in type 2 diabetic patients might certainly be a consequence of the well-demonstrated defective activation of this signalling pathway in response to hyperinsulinaemia in the skeletal muscle of these patients [29,30,37].…”
Section: Discussionsupporting
confidence: 52%
“…Besides hypoxia, STRA13 can be induced by a variety of other stimuli, such as TGF-b (Zawel et al, 2002), cytokines (Ivanova et al, 2004), retinoic acid (Boudjelal et al, 1997), insulin (Yamada et al, 2003) and light (Honma et al, 2002). It appears that in many of these seemingly disparate physiological contexts, STRA13 0 s main function is relaying suppressive environmental signals to STAT1 and other ISRE-containing genes.…”
Section: Discussionmentioning
confidence: 99%